Catheter Related Leuconostoc Mesenteroides Bacteremia: A Rare Case and Review of the Literature - Adem Karbuz; Bilge Aldemir Kocabaş; Aytaç Yalman; Zarife Kuloğlu; Ahmet Derya Aysev; Ergin Çiftçi; Erdal İnce (Galenos Yayinevi, 2017)
Herein we report the successful treatment of catheter related blood stream infections due to Leuconostoc mesenteroides with antibiotic lock therapy in addition to systemic treatment. With our case, we have shown that in the presence of catheter related blood stream infections, antibiotic lock therapy can be used as a therapeutic option to get successful results if the catheter cannot be removed or there are still positive cultures despite the systemic antibiotic therapy.